Recent advances in the understanding of enterovirus A71 infection: a focus on neuropathogenesis. Issue 6 (3rd June 2021) - Tee, Han Kang; Zainol, Mohd Izwan; Sam, I-Ching; Chan, Yoke Fun
ABSTRACT: Introduction : Hand, foot, and mouth disease caused by enterovirus A71 (EV-A71) is more frequently associated with neurological complications and deaths compared to other enteroviruses. Areas covered : The authors discuss current understanding of the neuropathogenesis of EV-A71 based on various clinical, human, and animal model studies. The authors discuss the important advancements in virus entry, virus dissemination, and neuroinvasion. The authors highlight the role of host immune system, host genetic factors, viral quasispecies, and heparan sulfate in EV-A71 neuropathogenesis. Expert opinion : Comparison of EV-A71 with EV-D68 and PV shows similarity in primary target sites and dissemination to the central nervous system. More research is needed to understand cellular tropisms, persistence of EV-A71, and other possible invasion routes. EV-A71 infection has varied clinical manifestations which may be attributed to multiple receptors usage. Future development of antivirals and vaccines should target neurotropic enteroviruses. Repurposing drug and immunomodulators used in combination could reduce the severity of EV-A71 infection. Only a few drugs have been tested in clinical trials, and in the absence of antiviral and vaccines (except China), active virus surveillance, good hand hygiene, and physical distancing should be advocated. A better understanding of EV-A71 neuropathogenesis is critical for antiviral and multivalent vaccines development.